Collective Dreams : Political Imagination and Community - McBride, Keally D. (Book collections on Project MUSE., 2005)
How do we go about imagining different and better worlds for ourselves? Collective Dreams looks at ideals of community, frequently embraced as the basis for reform across the political spectrum, as the predominant form of political imagination in America today. Examining how these ideals circulate without having much real impact on social change provides an opportunity to explore the difficulties of practicing critical theory in a capitalist society. Different chapters investigate how ideals of community intersect with conceptions of self and identity, family, the public sphere and civil society, and the state, situating community at the core of the most contested political and social arenas of our time. Ideals of community also influence how we evaluate, choose, and build the spaces in which we live, as the author's investigations of Celebration, Florida, and of West Philadelphia show. Following in the tradition of Walter Benjamin, Keally McBride reveals how consumer culture affects our collective experience of community as well as our ability to imagine alternative political and social orders. Taking ideals of community as a case study, Collective Dreams also explores the structure and function of political imagination to answer the following questions: What do these oppositional ideals reveal about our current political and social experiences? How is the way we imagine alternative communities nonetheless influenced by capitalism, liberalism, and individualism? How can these ideals of community be used more effectively to create social change?